Consumer personality and individual differences: Revitalizing a temporarily abandoned field - Bošnjak, Michael; Galešić, Mirta; Tuten, Tracy; Bratko, Denis (2007)
The editorial introduces the special issue on ‘ Consumer Personality and Individual Differences’ and gives an overview of the ten papers included. New developments in the following areas are addressed: (1) hierarchical personality models applied to consumer behavior, (2) brand personality research, (3) the role of individual difference measures as moderators of outcome variables relevant in consumer and advertising research, and (4) customer segmentation.
Projekt MZOS
ENG